Intercropping bananas with coffee and trees: Prototyping agroecological intensification by farmers and scientists - Staver, Charles; Bustamante, Oscar Enrique; Siles, Pablo; Aguilar, Carlos; Quinde, Karina; Castellón, Juan; Somarriba, Francisco; Tapia, Andrés; Brenes, Silvia; Deras, Marvin; Matute, Nelly (International Society for Horticultural Science (ISHS), 2025)
Bananas are often grown in mixed cropping systems. In Latin America, small growers cultivate bananas with minimal labor and purchased inputs in shaded coffee as a source of monthly income to supplement annual coffee sales. We deployed the framework of agroecological intensification in collaboration with six groups of small coffee growers in Costa Rica, Honduras, Nicaragua and Peru to assess the potential to improve the productivity of banana in mixed systems. After a formal diagnostic study of 30 smallholder coffee farms in each site carried out by scientists, farmer experimentation groups in the same sites did their own diagnostic sampling and identified priority areas for experimentation. Scientists and farmers developed prototypes for system improvement, and alternative management approaches of system components, labor and inputs. Across pilot zones, ‘Gros Michel’ was the most common cultivar, with banana mat density from 300 to 600 mats/ha with 950 to 1200 pseudostems/ha. Tree density varied from 150 to 550 trees/ha with available light ranging from 50 to 70%, and from 35 to 45% for banana and coffee. Farmer priorities across zones were similar: tree, banana and coffee resource partitioning; improved nutrition; coffee pruning; Fusarium wilt management; and marketing for better banana prices. Prototypes for testing addressed: light partitioning among trees, bananas and coffee; an input-output analysis of nutrients to increase the contribution of nitrogen from shade trees and reorient purchased nutrients; a shifting framework of Fusarium wilt management to address quarantine and cultivar substitution; and a marginal return analysis for step-wise intensification of the system, including banana.